THE EFFECT OF MANAGERIAL EFFECTIVENESS AND WORK ETHICS ON THE PERFORMANCE OF MADRASAH IBTIDAIYAH TEACHERS IN CIPUTAT SUB-DISTRICT, TANGERANG SELATAN CITY - Rani MARTIANI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2019)
Performance is the result of work and the progress that has been made by someone in their field of work. In achieving good result it needs to be supported by managerial effectiveness and a good work ethic between each person has an influence in improving teacher performance Elementary Islamic School at Ciputat, Tangerang City. The population in this study amounted to 220 teachers, taking research samples using sample random sampling techniques using Slovin formula so that there were 142 teachers. Data is empirical data obtained from questionnaires that have been tested for validity and reliability. The collected data was anakyzed by descriptive analysis, then the hypothesis used path analysis.The results of the study show that there is a Principal Management Effectiveness that has a positive direct on performance. Work Ethics has a positive direct effect on performance. Principal Management Effectiveness has a positive direct effect on the Work Ethic. The research implications are to improve the managerial effectiveness of principals and a good work ethic in achieving good performance.